Efforts to Build Village Community Awareness in Supervising the Use of Village Funds - Prakoso, Abdul Rahman (Law Research Review Quarterly, 2019)
Corruption becomes one of the big problems in a country. Indonesia as a unitary state with thousands of islands stretching from the tip of Sabang to Merauke. Development in Indonesia that continues to progress significantly is driven by synergistic government and society to build the nation. Overall development of infrastructure and human resources development. Infrastructure is a big project in the current administration. Many facilities are built using state money to the lowest level of government, namely village government. Villages as the spearhead of development have an important position to disburse village funds. Some development projects in the village that cause pros and cons in the community. Projects funded with village funds sometimes differ between the budget and reports provided with the results obtained from the development. So this is detrimental to the village community who cannot enjoy the results of government development. The community needs to oversee the running of village funds so that infrastructure development using village funds can be directly monitored.